Fracture and dislodgment of a guidewire retrieved by a Solitaire AB neurovascular remodeling device - Liu, Zhengli; Zhao, Boxiang; He, Xu; Gu, Jianping; Gong, Maofeng; Kong, Jie (Frontiers in Materials, 2023)
Background: Guidewire fracture and dislodgment are very rare but can cause serious complications. Method: A case was reported where part of the guidewire was blocked to the posterior tibial. We attempted to remove it using a Solitaire AB Neurovascular Remodeling Device. Result: A Solitaire AB Neurovascular Remodeling Device was successfully used to remove the fracture and dislodgment of a guidewire. There were no complications during the removal of the guidewire. Conclusion: A Solitaire AB can be used to remove a fractured guidewire, which is a simple and effective method to reduce complications. The Solitaire stent gradually crimped and tightened to form a dense inverted conical meshwork, similar to the “trans embolic protection device.” We can use minimally invasive methods to remove a broken and displaced guidewire within the vascular lumen.